Apoptotický gastrointestinální stromální tumor--AGIST - Bednár, B (Ceskoslovenska patologie, 1992)
Leiomyoma with a faint desmin positivity was identified among gastrointestinal stromal tumours. In addition to smooth muscle cells it was characterized by particular sausage-like strongly oxyphilic structures. The structures may have represented partially degraded tumour cells as well as insudative fibrinoid changes of intersititial collagen. Apoptotic bodies could be compared with Rosenthal fibres, Civatte bodies and other apoptotic phenomena. They were typical for described tumour and therefore it was recommended to classify it as "apoptotic gastrointestinal stromal tumour".
Keywords: apoptóza; Leiomyoma; gastrointestinální nádory; Humans; leiomyom; lidé; Apoptosis; Gastrointestinal Neoplasms